Organic matter identifies the nano-mechanical properties of native soil aggregates - Ed Dudley (Nanoscale, 2018)
Nanoscale mechanical properties of soil organic matter has been linked to macroscale soil behaviour via optimising QNM-AFM for rough and heterogeneous surface analysis, specifically intact soil micro-aggregates and particles.